2006
DOI: 10.1002/nbm.1039
|View full text |Cite
|
Sign up to set email alerts
|

Identification of diffuse and focal brain lesions by clinical magnetic resonance spectroscopy

Abstract: The purpose of this paper is to facilitate the comparison of magnetic resonance (MR) spectra acquired from unknown brain lesions with published spectra in order to help identify unknown lesions in clinical settings. The paper includes lists of references for published MR spectra of various brain diseases, including pyogenic abscesses, encephalitis (herpes simplex, Rasmussen's and subacute sclerosing panencephalitis), neurocysticercosis, tuberculoma, cysts (arachnoid, epidermoid and hydatid), acute disseminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 119 publications
3
26
1
Order By: Relevance
“…However, just as blood lactate levels have only a moderate sensitivity for mitochondrial disease, brain Lac peaks on MRS are also not highly sensitive. Two studies showed the sensitivity of Lac peaks in mitochondrial disease to be 18 % to 27% [34,35]. Lac peaks vary depending on whether a patient is undergoing an exacerbation of their disease [30], as well as whether their lesions are acute, subacute, or chronic [28].…”
Section: Mrs-based Central Nervous System Biochemical Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…However, just as blood lactate levels have only a moderate sensitivity for mitochondrial disease, brain Lac peaks on MRS are also not highly sensitive. Two studies showed the sensitivity of Lac peaks in mitochondrial disease to be 18 % to 27% [34,35]. Lac peaks vary depending on whether a patient is undergoing an exacerbation of their disease [30], as well as whether their lesions are acute, subacute, or chronic [28].…”
Section: Mrs-based Central Nervous System Biochemical Analysismentioning
confidence: 99%
“…Lac peaks vary depending on whether a patient is undergoing an exacerbation of their disease [30], as well as whether their lesions are acute, subacute, or chronic [28]. Detection of Lac signal may also depend on its concentration, as the threshold of detection by MRS is 0.5 mM to 1 mM [34,35]. Absence of a Lac peak similarly does not ruleout mitochondrial disease, as the specific tissues involved in mitochondrial disease vary, as does the location of brain involvement.…”
Section: Mrs-based Central Nervous System Biochemical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Mobile lipids, visible on MRS, can be seen in various acquired disorders, such as areas of necrosis within highgrade brain tumors (Kimura et al 2004;Delorme and Weber 2006), active lesions from demyelinating diseases such as multiple sclerosis (Wolinsky et al 1990;Near 2013), and infectious etiologies as in tuberculomas and toxoplasmosis (Kingsley et al 2006). Care should also be taken not to place the voxel too close to the skull, as this will capture the resonance from fat molecules in the diploe and scalp (Caruso et al 2004;Near 2013).…”
Section: Discussionmentioning
confidence: 99%